A comparative analysis of clinicopathological features of HPV-associated and HPV-independent cervical carcinomas based on P16 INK4a immunohistochemistry: A one-year retrospective study - Padmavathi D. Chaganti; Kaumudi Konkay; Ann M. Varghese (Indian Journal of Pathology and Microbiology)
The recent WHO classification of female genital tracts recommends cervical carcinomas to be further subtyped as HPV-associated and HPV-independent and accepted p16 immunoreactivity as a surrogate biomarker for HPV testing. This paper presents the clinicopathological spectrum of cervical carcinomas in correlation with p16 immunoreactivity. Aims and Objectives: This study aims to evaluate the immunoreactivity of p16 in cervical carcinoma, subtype them into HPV-associated and HPV-independent based on p16 immunoreactivity, and correlate them with clinicopathological features. Design: A hospital-based retrospective study of one-year duration was done after ethics approval. A total of 124 cases were identified, and various parameters like the presence of mitosis, lymphovascular invasion, tumor budding, tumor-infiltrating lymphocytes, the pattern of stromal invasion, and the pattern of necrosis were recorded and graded. Immunohistochemistry (IHC) with p16 marker was done in 40 cases, and immunoreactivity was correlated with clinical and histopathological parameters. Statistical Analysis: Multivariate analysis was done with Fisher’s exact test, and a P value of <0.05 was considered significant. Results: P16 was positive in 36 out of 40 cases which included 35 cases of squamous cell carcinoma (SCC) (keratinizing—14 out of 35 SCC, 11 positive out of these 14, non-keratinizing-21 out of 35 SCC, 20 positive, out of these 21), two cases of adenocarcinoma (both positive), two cases of adenosquamous carcinoma (both positive), and one case of small cell neuroendocrine carcinoma (positive). p16 negative in four cases (10%) (keratinizing type-3, non-keratinizing—1). P value was significant for HPV-independent carcinoma and keratinizing SCC morphology. The P value was not significant when p16 positivity with other parameters. Conclusion: HPV-associated were 90%, HPV-independent were 10%.